2023
DOI: 10.1186/s12873-023-00772-3
|View full text |Cite
|
Sign up to set email alerts
|

Not only COVID-19 disease impacts ambulance emergency demands but also lockdowns and quarantines

Abstract: Background The pandemic has impacted both patients infected by the SARS-CoV-2 virus and patients who seek emergency assistance due to other health issues. Changes in emergency demands are expected to have occurred during the pandemic, the objective of this investigation is to characterize the changes in ambulance emergency demands during the first year of the COVID-19 pandemic in the Vaud State of Switzerland. The goal of this research is to identify the collateral effects of the COVID-19 pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…However, we found that new urgent diagnoses also decreased, such as stroke and acute myocardial infarction, among others. 20 , 29 Likewise, it is noteworthy that several countries such as China, Italy, France, and the USA have reported a decrease in the provision of health care and in the diagnosis of new cases of stroke and acute myocardial infarction which reflects the trends observed in our study. 34–37 In addition, the decrease in hospital emergency department utilization may be attributed to patient concern about possible SARS-CoV-2 contamination if transferred to the hospital.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, we found that new urgent diagnoses also decreased, such as stroke and acute myocardial infarction, among others. 20 , 29 Likewise, it is noteworthy that several countries such as China, Italy, France, and the USA have reported a decrease in the provision of health care and in the diagnosis of new cases of stroke and acute myocardial infarction which reflects the trends observed in our study. 34–37 In addition, the decrease in hospital emergency department utilization may be attributed to patient concern about possible SARS-CoV-2 contamination if transferred to the hospital.…”
Section: Discussionsupporting
confidence: 81%
“…Some studies described a reduction in new diagnosis of hypertension, diabetes, and COPD in agreement with our results. 25 , 28 , 29 As evidenced in both the existing literature and our routine clinical practice, the decline in the incidence of chronic diseases can be ascribed to a combination of factors, including widespread mobility restrictions imposed throughout the country. Additionally, patients displayed a hesitancy to seek face-to-face medical care both during and even after the lifting of restrictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Coronavirus (COVID19) pandemic had major implications for emergency medical communication centres (EMCC) [1][2][3] which had to be reorganised to respond effectively to the large influx of telephone calls from patients presenting with influenza-like illness and dyspnoea [4][5][6]. Although online triage systems have been developed [7,8], the increase in calls to EMCCs due to the large number of respiratory distress situations was very significant [9]. Some EMCCs developed a two-tiered response, where the first tier performed the initial triage (differentiating between sick/notsick and mild/severe symptoms) and the second tier was comprised of clinicians (emergency physicians, advanced practice nurses or advanced paramedics) who assessed more complex and severe cases [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…The Coronavirus (COVID-19) pandemic had major implications for emergency medical communication centres (EMCC) [ 1 , 2 , 3 ], which had to be reorganised to respond effectively to the large influx of telephone calls from patients presenting with influenza-like illness and dyspnoea [ 4 , 5 , 6 ]. Although online triage systems were developed [ 7 , 8 ], the increase in calls to EMCCs due to the large number of respiratory distress situations was very significant [ 9 ]. Some EMCCs developed a two-tiered response, where the first tier performed the initial triage (differentiating between sick/not-sick and mild/severe symptoms) and the second tier was comprised of clinicians (emergency physicians, advanced practice nurses or advanced paramedics) who assessed more complex and severe cases [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%